2016
DOI: 10.1038/aps.2016.104
|View full text |Cite
|
Sign up to set email alerts
|

A novel matrine derivate inhibits differentiated human hepatoma cells and hepatic cancer stem-like cells by suppressing PI3K/AKT signaling pathways

Abstract: Matrine is an alkaloid extracted from a Chinese herb Sophora flavescens Ait, which has shown chemopreventive potential against various cancers. In this study, we evaluated the anticancer efficacy of a novel derivative of matrine, (6aS, 10S, 11aR, 11bR, 11cS)-10- methylamino-dodecahydro- 3a,7a-diazabenzo (de) (MASM), against human hepatocellular carcinoma (HCC) cells and their corresponding sphere cells in vitro and in vivo. Human HCC cell lines (Hep3B and Huh7) were treated with MASM. Cell proliferation was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Surgical resection and liver transplantation, which are the current gold standards for the treatment of HCC, are less than satisfactory due to metastasis and high recurrence rates ( 20 ). Matrine has been confirmed as a natural anti-tumor agent against several types of cancer, including acute myeloid leukemia, prostate cancer, lung cancer and human hepatoma ( 21 24 ). Nevertheless, the anti-metastatic effect of matrine and its associated mechanism(s) in HCC remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection and liver transplantation, which are the current gold standards for the treatment of HCC, are less than satisfactory due to metastasis and high recurrence rates ( 20 ). Matrine has been confirmed as a natural anti-tumor agent against several types of cancer, including acute myeloid leukemia, prostate cancer, lung cancer and human hepatoma ( 21 24 ). Nevertheless, the anti-metastatic effect of matrine and its associated mechanism(s) in HCC remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the IC 50 value of MS0 was nearly 6 times higher than that of FK866 (9.08±0.90 vs 1.60±0.32 nmol/L) ( Figure 1B and 1C). Furthermore, we examined their effects on the cell viability of a hepatocellular carcinoma cell line, HepG2, using the cell counting kit-8 (CCK-8) method [22] . The difference between the IC 50 value of MS0 (IC 50 =510.01±162.09 nmol/L) and FK866 (IC 50 =2.21±0.21 nmol/L) is nearly 250-fold ( Figure 1D and 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin regulation and the PI3K/AKT signaling pathways are increasingly associated with cell proliferation in various cancers ( 28 30 ). Among the high-grade gliomas, the grade IV astrocytic tumor known as glioblastomas (GBM) is the most common, aggressive, and deadly tumor.…”
Section: Discussionmentioning
confidence: 99%